A survey of response of access services in academic libraries to COVID-19. Issue 2 (3rd April 2021) - Tolppanen, Bradley P.
Abstract: This article presents the results of an online survey of access services departments at academic libraries on the responses implemented during the initial stage of COVID-19 in March–May 2020. The 33-question survey was completed by 121 respondents. The article identifies policies and procedures adopted by access services departments during the pandemic, including staffing, return of library materials, fines, due dates, quarantine periods, interlibrary loan, reserves, and retrieval of materials.